2011
DOI: 10.1042/bj20110558
|View full text |Cite
|
Sign up to set email alerts
|

Glu106 in the Orai1 pore contributes to fast Ca2+-dependent inactivation and pH dependence of Ca2+ release-activated Ca2+ (CRAC) current

Abstract: FCDI (fast Ca²⁺-dependent inactivation) is a mechanism that limits Ca²⁺ entry through Ca²⁺ channels, including CRAC (Ca²⁺ release-activated Ca²⁺) channels. This phenomenon occurs when the Ca²⁺ concentration rises beyond a certain level in the vicinity of the intracellular mouth of the channel pore. In CRAC channels, several regions of the pore-forming protein Orai1, and STIM1 (stromal interaction molecule 1), the sarcoplasmic/endoplasmic reticulum Ca²⁺ sensor that communicates the Ca²⁺ load of the intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 31 publications
9
52
0
Order By: Relevance
“…Recently, the glutamate residue E106 in Orai1 has been identified to contribute to the extracellular pH dependence of Ca 2+ release-activated Ca 2+ (CRAC) channels [48]. Here, we demonstrate that two aspartate residues in the first extracellular loop of Orai1, close to E106, also contribute to the pH-induced changes of I CRAC .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, the glutamate residue E106 in Orai1 has been identified to contribute to the extracellular pH dependence of Ca 2+ release-activated Ca 2+ (CRAC) channels [48]. Here, we demonstrate that two aspartate residues in the first extracellular loop of Orai1, close to E106, also contribute to the pH-induced changes of I CRAC .…”
Section: Discussionmentioning
confidence: 54%
“…Close to the glutamate residue in position 106 (E106), which has already been shown to mediate some pH dependence [48], the first extracellular loop of Orai1 reveals two additional negatively charged residues: aspartate residues D110 and D112. An Orai1 construct in which these two aspartates were mutated to uncharged alanine residues (D110/112A) demonstrated that these residues contribute to the ion selectivity and to the anomalous mole-fraction behavior of Orai1 channels [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, E106 accounts for Ca 2+ selectivity in Orai1 and can be blocked by extracellular protons 202 . This class of inhibitor includes SB01990, SPB06836, KM06293 and RH01882, which all present the capability to alter the pore geometry of Orai1 and diminishes SOCE 164 .…”
Section: Drugs Targeting Ca2+ Channels/transporters/pumps For Cancer mentioning
confidence: 99%
“…2D) were ϳ0.75 for STIM1 WT and ϳ0.78 for STIM1 DQ. To compare Ca 2ϩ -dependent inactivation and potentiation of I CRAC mediated by STIM1 WT/Orai1 and STIM1 DQ/Orai1 over the entire voltage range, we constructed apparent P o curves from normalized tail currents at Ϫ100 mV as previously described (31,32). Transfected with similar S1/O1 DNA ratios, STIM1 WT and STIM1 DQ currents showed both potentiation (points above dashed line corresponding to the apparent P o at 80 mV, set to unity) and inactivation (points below dashed line) in 10 mM [Ca 2ϩ ] o (Fig.…”
Section: Mutagenesis Of Stim1 N-glycosylation Sites Profoundlymentioning
confidence: 99%